The Effect of COVID-19 Pandemic-Induced Stress on Reproductive-Age Women's Menstrual Cycle Regularity - Hamid, Ruaa Abduljabbar; Fathi, Zahra Noah; Al-Wazzan, Raida (UI Scholars Hub, 2022)
Intense stress resulting from major life events can affect women's menstrual cycle. The current Coronavirus Disease 2019 (COVID-19) pandemic, impacting various sectors, is considered a major form of stress. During May-November 2020, some women in Iraq have experienced menstrual disruptions, which can happen whether they get infected with the COVID-19 or simply deals with pandemic-induced stress. Thus, this study aimed to evaluate the effect of the COVID-19 pandemic-induced stress on menstrual cycle regularity of reproductive-age women. This study used an observational cross-sectional design conducted in Iraq from May to November 2020. A sample of 500 reproductive-age women filled out an online questionnaire about their menstrual records and psychological stress levels using a Perceived Stress Scale-10 for three months during the pandemic. A comparison between menstrual cycle irregularity and stress levels before and during the pandemic was done with a p-value of <0.05 and statistically significant. It was found that 47.72% of women had irregular menstrual cycles and high perceived stress scales during the pandemic compared to 20.94% with irregular cycles and high-stress levels before the pandemic. In brief, the high-stress level induced by the COVID-19 pandemic is associated with the irregular menstrual cycle in the sampled reproductive-age women.